Technology Makes the Heart Grow Fonder? A Test of Media Multiplexity Theory for Family Closeness - Bhoj Balayar; Michael Langlais (Social Sciences, 2021)
Technology can be helpful for family relationships. Media multiplexity theory illustrates that the more technological connections (i.e., multimodality) an individual has with their family members, the stronger that relationship. Yet, this theory assumes that spending time face to face (FtF) is equitable to multimodality for relationship quality. The goal of this study is to examine the impact of online and offline interactions for the quality of family relationships. Data are from undergraduate students completing an online survey (N = 154). Results reveal that spending time FtF is better for the quality of relationships for one parent, but not the other. Although FtF was not significantly different for grandparent and sibling relationships, participants felt closer to siblings when they texted. Correlational analyses revealed that individuals scoring high in collectivism report that spending time FtF is associated with higher relationship closeness and love, particularly with parents, but not other family members. These results provide some evidence for the importance of spending quality time with family members, particularly for those who identify as collectivistic.